O Programa de Aquisição de Alimentos (PAA) no acampamento Elizabeth Teixeira Limeira-SP: acesso, possibilidades e limitações. - Gil Jimenez Fernandes, Karla Elizabeth (2017)
Food security has been a constant concern in the world since the mid-twentieth century, manifested by world leaders in the post-war period and materialized in the holding of the United Nations Conference on Agriculture and Food in the creation of the United Nations Food and Agriculture Organization ( FAO) in October 1945. Food and nutritional security has emerged as a matter of great importance and interest, as it is the means that seeks to guarantee the right to food for people and individuals, with an emphasis on the most vulnerable groups. To improve the efficiency of Food and Nutrition Security, it is necessary to create opportunities for follow-up, monitoring and evaluation of public policies that allow to guarantee impacts at their levels. This is not possible without the participation of government agencies, civil society, private sector and international cooperation in the whole process from conception to evaluation. . The PAA is a component program of a set of public policies related to the fight against hunger and poverty. Its objective is to enable improvements in the socioeconomic indicators of farmers' families, thus helping to improve their quality of life. It is concluded that there is still much to improve the PAA program at the Elizabeth Teixeira camp. There are many shortcomings that make the PAA program not have the impact it should have.